Extracellular vesicles-coupled miRNAs from oviduct and uterus modulate signaling pathways related to lipid metabolism and bovine early embryo development - Rosane Mazzarella; Karina Cañón-Beltrán; Yulia N. Cajas; Meriem Hamdi; Encina M. González; Juliano C. da Silveira; Claudia L. V. Leal; D. Rizos (Journal of Animal Science and Biotechnology, 2024)
Abstract Background Extracellular vesicles (EVs) present in oviductal (OF) and uterine fluid (UF) have been shown to enhance bovine embryo quality during in vitro culture by reducing lipid contents and modulating lipid metabolism-related genes (LMGs), while also influencing cell proliferation, suggesting their involvement on the regulation of different biological pathways. The regulation of signaling pathways related to cell differentiation, proliferation, and metabolism is crucial for early embryo development and can determine the success or failure of the pregnancy. Bioactive molecules within EVs in maternal reproductive fluids, such as microRNAs (miRNAs), may contribute to this regulatory process as they modulate gene expression through post-transcriptional mechanisms. Results This study evaluated miRNA cargo in OF-EVs from the early luteal phase and UF-EVs from the mid-luteal phase, coinciding with embryo transit within oviduct and uterus in vivo, and its possible influence on LMGs and signaling pathways crucial for early embryo development. A total of 333 miRNAs were detected, with 11 exclusive to OF, 59 to UF, and 263 were common between both groups. From the 20 differentially expressed miRNAs, 19 up-regulated in UF-EVs (bta-miR-134, bta-miR-151-3p, bta-miR-155, bta-miR-188, bta-miR-181b, bta-miR-181d, bta-miR-224, bta-miR-23b-3p, bta-miR-24-3p, bta-miR-27a-3p, bta-miR-29a, bta-miR-324, bta-miR-326, bta-miR-345-3p, bta-miR-410, bta-miR-652, bta-miR-677, bta-miR-873 and bta-miR-708) and one (bta-miR-148b) in OF-EVs. These miRNAs were predicted to modulate several pathways such as Wnt, Hippo, MAPK, and lipid metabolism and degradation. Differences in miRNAs found in OF-EVs from the early luteal phase and UF-EVs from mid-luteal phase may reflect different environments to meet the changing needs of the embryo. Additionally, miRNAs may be involved, particularly in the uterus, in the regulation of embryo lipid metabolism, immune system, and implantation. Conclusions Our study suggests that miRNAs within OF- and UF-EVs could modulate bovine embryo development and quality, providing insights into the intricate maternal-embryonic communication that might be involved in modulating lipid metabolism, immune response, and implantation during early pregnancy.